The effects of changing pace on metabolism and stroke characteristics during high-speed breaststroke swimming - Thompson, K. G.; MacLaren, D. P.; Lees, A.; Atkinson, G. (Journal of Sports Sciences, 2004)
Performances often vary between the heats and finals of breaststroke swimming competitions possibly because the swimmers try to conserve their energy, or for other tactical reasons. Additionally, coaches might advise either a 'positive' or 'even' pace race strategy during the final. The effect of such pacing changes on metabolism (blood lactate, heart rate, ventilation), ratings of perceived exertion, stroke kinematics and turning times have not been investigated. Nine male competitive breaststroke swimmers swam three paced (Aquapacer) 200-m trials, 48 h apart and in random order, at 98%, 100% and at an attempted 102% of their maximal 200-m time-trial speed. Responses in metabolic variables were similar between the 98% and 100% trials, but higher post-exercise blood lactate concentrations and respiratory exchange ratios were observed following the 102% trial. As the pace of trials increased, stroke rate was found to increase proportionately with stroke count. However, during the latter stages of the 100% trial, a disproportionate increase in the stroke count was observed, which led to a significant pacing error. This feature was more obvious in the 102% trial, where participants demonstrated 'positive pacing' and reported higher ratings of perceived exertion than for the 98% trial. During the early stages of the trials, turning times were initially shorter the faster the pace of the trial; however, as the trials progressed, this pattern was found to reverse. We conclude that a slight reduction in pace during near maximal breaststroke swimming altered kinematic but not post-exercise metabolic responses, while an increase in pace led to positive pacing and an increase in both kinematic responses and anaerobic metabolism.